Study the Chemical Composition of Essential Oil of Ginger (Zingiber officinale) and Antioxidant and Cell Toxicity - HR Amiri; M Mohammadi; S Sadatmand; Taheri E (Institue of Medicinal Plants, ACECR, 2016)
Background: Ginger Zingiber officinale has been used as a medicine since ancient times. Objective: This study has been concentrated on identification of chemical compositions of essential oils of Indian and Chinese gingers. Also, antioxidant and cytotoxic activities of Chinese oil were determined. Methods: The first species was collected from India Province and other was purchased from Iranian markets. The essential oils were obtained by Hydrodistillation in a Clevenger type apparatus and were dried over anhydrous Sodium Sulphat. The yields of essential oils were 1.45 and 1.3% w/w, respectively. Then, the oils stored at +4°C in the dark place until analysis. The chemical compositions of essential oils were analysis by GC and GC/MS method. The identification of the essential oils components was based on calculation of retention Indices and comparison of mass spectra with standards. The Chinese oil was subjected to screening for its possible antioxidant and cytotoxic activities by means DPPH and MTT assays, respectively. Results: 46 constituents were identified in the essential oils. The major constituents of Indian species were α-Zingiberene (28.25%) β-Sesquiphellandrene (15.65%), α-Curcumene (15.23%) and trans-γ-Cadinene (11.88%). In Chinese species α-Zingiberene (35.67%) β-Sesquiphellandrene (15.27%), trans-γ-Cadinene (9.25%) and E-Citral (6.0%) were main components. In the DPPH test and the MTT test systems, the IC50 values of Iranian ginger essential oil were 80.7 and 72.6 µg/ml, respectively. Conclusion: The main class of the compounds were found in these species to be sesquiterpenes. Chinese ginger essential oil exhibited the strong cytotoxicity and antioxidant activity at low concentration.